Vestibular Influence on Vertebrate Skeletal Symmetry and Body Shape - Gordy, Clayton; Straka, Hans (Frontiers in Systems Neuroscience, 2021)
Vestibular endorgans in the vertebrate inner ear form the principal sensors for head orientation and motion in space. Following the evolutionary appearance of these organs in pre-vertebrate ancestors, specific sensory epithelial patches, such as the utricle, which is sensitive to linear acceleration and orientation of the head with respect to earth’s gravity, have become particularly important for constant postural stabilization. This influence operates through descending neuronal populations with evolutionarily conserved hindbrain origins that directly and indirectly control spinal motoneurons of axial and limb muscles. During embryogenesis and early post-embryonic periods, bilateral otolith signals contribute to the formation of symmetric skeletal elements through a balanced activation of axial muscles. This role has been validated by removal of otolith signals on one side during a specific developmental period in Xenopus laevis tadpoles. This intervention causes severe scoliotic deformations that remain permanent and extend into adulthood. Accordingly, the functional influence of weight-bearing otoconia, likely on utricular hair cells and resultant afferent discharge, represents a mechanism to ensure a symmetric muscle tonus essential for establishing a normal body shape. Such an impact is likely occurring within a critical period that is curtailed by the functional completion of central vestibulo-motor circuits and by the modifiability of skeletal elements before ossification of the bones. Thus, bilateral otolith organs and their associated sensitivity to head orientation and linear accelerations are not only indispensable for real time postural stabilization during motion in space but also serve as a guidance for the ontogenetic establishment of a symmetric body.